Picturing victory: the visual imaginary of the War of Resistance, 1937-1947 - Mitter, R (Brill, 2008)
The Sino-Japanese War of 1937-1945 has not been sufficiently understood as a narrative in its own right, but rather, as a transitional conflict between Nationalist and Communist rule. The examination of the visual imagery of warfare disseminated through newsprint and books is one way to reinterpret the history of this period. Through a close reading of images printed in a Shanghai newspaper, Zhonghua ribao, during the final days of the battle for the city in 1937, we see how the news was shaped to impose a narrative of order with a positive teology at a time when China was plunged into chaos with no guarantee of the eventual outcome of the war. The nature of this narrative is explored through examination of images of the body, as well as the positioning of images in the context of the printed page. The conclusion then contrasts these images with a pictorial history of the Sino-Japanese War published during the Civil War, in 1947. It suggests that although this book is able to bring narrative closure to the earlier conflict, its own narrative is imbued with an unease caused by the reality of the new war that had broken out within months of the ending of the war against Japan, and suggests that narrative closure is never truly obtained.